Screening of the Risk of Eating Disorders Among Medical Students in the MENA region and Its Associated Factors: A Multinational Cross‐Sectional Study - Siwar Belhaj Salem; Fatima Ezzahraa El Idrissi; Ahmed Fikry mohamed; Husam Khrais; Rawan Elwalid Jad; Umair Ul Haq; Jaafer Ammar Jouini; Ramla Mohamed Farah Roble; Ronahy Haidar; Fatma Zaouali; Abdullah Janem; Hossam Salameh; et al. (Brain and Behavior)
ABSTRACT Background Eating disorders (EDs) are a group of mental diseases marked by disrupted eating behaviors, and are associated with several factors. Medical students are highly exposed to this mental disorder with a prevalence of 17.35% in 2022. Objective To evaluate the risk of EDs and its associated factors among medical students in the Middle East and North Africa (MENA) region. Methods A web‐based cross‐sectional study was conducted among medical students in the MENA region during the months of June and July 2024. The primary data collection instrument was a comprehensive questionnaire that contained the Eating Attitudes Test (EAT‐26) and sociodemographic and clinical features and designed using Google Forms and distributed via social media platforms. Results The total number of participants was 5061. The mean age in our population was 22.58 ± 3.27. Our population's average EAT‐26 score was 13.87 ± 10.7, with ranges varying from 0 to 72. Based on their EAT‐26 scores being 20 or above, 1254 people (24.8%) were deemed to be at risk of EDs. Among the participants, 8% were underweight. The multivariable logistic regression model revealed several eating disorder risk factors such as T1DM, schizophrenia, autism, female gender, IBD, and daily exposure to thin body ideal. Regular sports practice and weight satisfaction were protective factors. Conclusion There exists a higher prevalence of individuals at risk for the development of EDs in the MENA region especially females, students with comorbidities, and those having conflictual relationships with their parents. Regular sports practice and weight satisfaction are protective factors.